Bone-targeted therapy use in patients with bone metastases from lung cancer: A systematic review of randomized controlled trials. (November 2016) - LeVasseur, Nathalie; Clemons, Mark; Hutton, Brian; Shorr, Risa; Jacobs, Carmel
Highlights: Bone-targeted agents (BTAs) are infrequently used in metastatic lung cancer. BTAs are effective at delaying the annual incidence of SREs and time to first SRE. Quality of life is a rare endpoint in studies looking at bone-targeting agents. Adverse events with bone-targeting agents remain low and similar between agents. Abstract: Background: Patients with advanced lung cancer commonly have bone metastases. Compared with other malignancies, the use of bone-targeted agents (e.g. bisphosphonates and denosumab) is less common in lung cancer patients. This may be due to the perception that bone-targeted agents are less effective in this population. Objective: To perform a systematic review to evaluate data from randomized trials of bone-targeted agents in lung cancer patients with bone metastases. Methods: A systematic search of Medline, Embase and the Cochrane Register of Controlled Trials through May 2015 was performed. Randomized trials of bone-targeted therapies in lung cancer patients with bone metastases were sought. Outcomes studied included skeletal related events (SREs), pain, quality of life, progression-free survival and overall survival. Random effects meta-analyses were planned if studies were judged homogeneous. Results: Of 632 abstracts, 17 publications describing 13 studies were included. Sample sizes ranged between 50 and 1776. Of 3379 patients, 1903 had lung cancer, with subgroup data available for 8 of 13 studies. Patient demographics were comparable, but enrollment criteria and endpoints were heterogeneous across studies, precluding meta-analysis. Study-specific results suggested that bone-modifying agents reduce the incidence of SREs and bone pain in lung cancer patients. Three studies suggested a survival benefit. Conclusion: Data from included trials suggests benefit of bone-targeted agents in lung cancer for the prevention of SREs and bone pain. There is a trend toward improvement in overall survival and progression-free survival, although further research is needed. Impact on quality of life and key subgroups for benefit both require future research.